Hypergraph-based resource allocation for Device-to-Device underlay H-CRAN network - Pan Zhao; Wenlei Guo; Datong Xu; Zhiliang Jiang; Jie Chai; Lijun Sun; He Li; Weiliang Han (International Journal of Distributed Sensor Networks)
In the hybrid communication scenario of the Heterogeneous Cloud Radio Access Network and Device-to-Device in 5G, spectrum efficiency promotion and the interference controlling caused by spectrum reuse are still challenges. In this article, a novel resource management method, consisting of power and channel allocation, is proposed to solve this problem. An optimization model to maximum the system throughput and spectrum efficiency of the system, which is constrained by Signal to Interference plus Noise Ratio requirements of all users in diverse layers, is established. To solve the non-convex mixed integer nonlinear optimization problem, the optimization model is decomposed into two sub-problems, which are all solvable quasi-convex power allocation and non-convex channel allocation. The first step is to solve a power allocation problem based on solid geometric programming with the vertex search method. Then, a channel allocation constructed by three-dimensional hypergraph matching is established, and the best result of this problem is obtained by a heuristic greed algorithm based on the bipartite conflict graph and µ -claw search. Finally, the simulation results show that the proposed scheme improves the throughput performance at least 6% over other algorithms.